The influence of hydrothermal operation on the surface properties of kitchen waste-derived hydrochar: Biogas upgrading. (20th June 2020) - Zhou, Ying; Engler, Nils; Li, Yeqing; Nelles, Michael
Abstract: Kitchen waste (KW) when disposed properly we can still utilize its nutrients and energy through appropriate recycling process. KW-hydrochar is the major product from hydrothermal carbonization (HTC) which is regarded as a promising method in waste treatment. However, the studies which focus more about the factors in regulating the properties of hydrochar and its further influence were limited. Here, HTC temperature (195 °C, 225°Cand 255 °C) and retention time (1.5h, 4.5h, 9.0h and 12.0h) were chosen as the controlling factors to observe the influence in the surface property. Moreover, it is the first time to research the role of KW-hydrochar chemical structures in co-digestion to regulate the biogas and methane production. Meanwhile, KW-hydrochar had no further thermal treatment and its own gas production was taken into account. The results revealed that KW-hydrochar gained at 225 °C in 4.5h affected the increase in methane yield up to 19% in co-digestion. Not only the surface morphology but also some functional groups acted as key factors on this study. Redox active moieties and amine could affect the methanogenesis process in varying degrees. In the end, a sustainable pathway of "waste to clean energy" by using KW-hydrochar as an additive was proposed. Graphical abstract: Image 1 Highlights: KW-derived hydrochar used as additive in co-digestion could promote biogas yield. KW-hydrochar obtained in 4.5h (225 °C) could realize increasing CH4 yield up to 19%. Some redox active moieties may have an active effect on methanogenesis process. Functional group of amine may negatively affect the methane production upgrading. KW-hydrochar could improve waste to clean energy conversion efficiency.